PELAKSANAAN FUNGSI KOORDINASI DALAM MENINGKATKAN MUTU PELAYANAN (Studi Kasus Di Kantor Camat Landono Kabupaten Konawe Selatan) - Indriastuti, Gusti Agung Priska; Alam, Syamsul; Jopang, Jopang (Universitas Halu Oleo, 2020)
The coordination over the past two years in the Landono Sub-District Office has decreased, this is due to administrative problems having problems with technology that are sometimes not functioning properly and human resources are not yet fully qualified. Therefore, the public services provided to Landono Sub-district are still not optimal, with many complaints from the public who are dissatisfied with the services provided by the District of Landono.O Formulation of the problem How the Implementation of the Coordination Function in Improving Service Quality. in the Landono Sub-District Office, it is already good, as indicated by the implementation of staff briefings, social security meetings and maintenance of existing work relationships. Employees and leadership elements in the Landono Sub-District Office each other complement and assist in service work to the community and Quality Improvement Services are provided by all elements in the Landono Sub-District Office with improved facilities and infrastructure as well as the reliability of employees in providing services needed by the community and responsive and ready for all service work